The spatial relationship and distances of posterior root apices to various anatomical structures - Choo, Schzanne; Wey, Mang Chek; Ngeow, Wei Cheong; Chai, Wen Lin; Alam, Mohammad Khursheed (Japan International Cultural Exchange Foundation, 2018)
Objective: This study aimed to determine the spatial relationship and distances of the apices of posterior teeth to the maxillary sinus and mandibular canal/mental foramen. Materials and Methods: Thirty-two digital orthopantomograms were included, and exported to Adobe® Photoshop® CS3 version 10.0. The length of the crown and root of all posterior teeth were measured. Their roots were identified as being located 'away', 'in contact' or 'appear to project into' the sinus or mandibular canal/mental foramen. The bony distances between the apices of all posterior teeth and these anatomy structures were measured. All posterior teeth were present except for 18 missing maxillary third molars (R = 8, L = 10) and mandibular third molars (R = 9, L = 9) each. Results: There were 75.2% apices that appeared 'in contact' or 'projected into' the sinus, and this involved mainly the second premolar and all molars. In cases with measureable bony distances, the average distances (in mm) in away from the maxillary sinus were 5.61 at first premolar, 2.70 at second premolar, 1.66 at first molar, 2.29 at second molar and 3.28 at third molar. The average distance (in mm) away from the neurovascular structure in the mandible were 5.49 at first premolar, 5.00 at second premolar, 4.50 at first molar, 2.58 at second molar and 1.31 at third molar. Ten second molar apices (20.8%) and 31 apices (64.6%) of the third molar appeared to be 'in contact' with the mandibular canal. The mandibular premolars did not appear to be 'in contact' with the anterior loop or mental foramen. Conclusion: There appeared to be a closer proximity of the posterior teeth to the maxillary sinus than the mandibular canal/ mental foramen.